What matters to program partners when implementing a community-based exercise program for people post-stroke? A theory-based qualitative study and cost analysis - Aravind, Gayatri; Bashir, Kainat; Cameron, Jill I.; Bayley, Mark T.; Teasell, Robert W.; Howe, Jo-Anne; Tee, Alda; Jaglal, Susan B.; Hunter, Susan; Salbach, Nancy M. (Frontiers in Rehabilitation Sciences, 2023)
Background: Community-based exercise programs integrating a healthcare-community partnership (CBEP-HCP) can facilitate lifelong exercise participation for people post-stroke. Understanding the process of implementation from multiple perspectives can inform strategies to promote program sustainability. Purpose: To explore stakeholders’ experiences with undertaking first-time implementation of a group, task-oriented CBEP-HCP for people post-stroke and describe associated personnel and travel costs. Methods: We conducted a descriptive qualitative study within a pilot randomized trial. In three cities, trained fitness instructors delivered a 12-week CBEP-HCP targeting balance and mobility limitations to people post-stroke at a recreation centre with support from a healthcare partner. Healthcare and recreation managers and personnel at each site participated in semi-structured interviews or focus groups by telephone post-intervention. Interviews and data analysis were guided by the Consolidated Framework of Implementation Research and Theoretical Domains Framework, for managers and program providers, respectively. We estimated personnel and travel costs associated with implementing the program. Results: Twenty individuals from three sites (4 recreation and 3 healthcare managers, 7 fitness instructors, 3 healthcare partners, and 3 volunteers) participated. We identified two themes related to the decision to partner and implement the program: 1) Program quality and packaging, and cost-benefit comparisons influenced managers’ decisions to partner and implement the CBEP-HRP, and 2) Previous experiences and beliefs about program benefits influenced staff decisions to become instructors. We identified two additional themes related to experiences with training and program delivery: 1) Program staff with previous experience and training faced initial role-based challenges that resolved with program delivery, and 2) Organizational capacity to manage program resource requirements influenced managers’ decisions to continue the program. Participants identified recommendations related to partnership formation, staff/volunteer selection, training, and delivery of program activities. Costs (in CAD) for first-time program implementation were: healthcare partner (680); fitness coordinators and instructors (3,153); and participant transportation (personal vehicle: 283; public transit: 110). Conclusion: During first-time implementation of a CBEP-HRP, healthcare and hospital managers focused on cost, resource requirements, and the added-value of the program, while instructors and healthcare partners focused on their preparedness for the role and their ability to manage individuals with balance and mobility limitations.